Bioactivity and hemocompatibility of sol–gel bioactive glass synthesized under different catalytic conditions. (25th November 2020) - Durgalakshmi, D.; Rakkesh, R. Ajay; Aruna, P.; Ganesan, Singaravelu; Balakumar, S.
Abstract : In bioactive glass synthesis by sol–gel method, HCl catalyst induces biocompatible wollastonite crystallization and supports higher apatite formation. Abstract : Sol–gel prepared nanostructured bioactive glass has superior osteoconductivity compared to micron-sized bioactive glass materials. Herein, we report on the choice of acid catalysts in bioactive glass synthesized by the sol–gel method and its effect on altering the nanostructure, crystallization, and in vitro apatite. Bioactive glass-HNO3 has sodium calcium silicate (Na2 Ca2 Si3 O9 ) compounds after sintering. Whereas in the case of bioactive glass-HCl, wollastonite (CaSiO3 ) based crystals are formed in the silica network. At a very low immersion time of 8 h, the apatite formation on the surface of bioactive glass synthesized using HCl as a catalyst is 75% higher compared to bioactive glass synthesized using HNO3 . The intermediated washing and drying of sintered bioactive glass samples show enhanced apatite formation and negligible NaCl crystallization on the reactive surface. The results of the present work elaborate on the importance of the role of an acid catalyst in the sol–gel synthesis of nanostructured bioactive glass, which will be helpful for its large-scale production with enhanced bioactivity.